The Role and Impact of AI-Driven Feedback Models and Applications in EFL Vocabulary Learning and Retention: A Systemic Review - Khan, Dr. Raja Muhammad Ishtiaq; Shahbaz, Muhammad; Farid, Raja Zahid; Hamid, Nouman (UIN Salatiga, 2025)
Vocabulary learning is an essential part of language learning. Vocabulary Instruction Feedback is essential in achieving learning objectives, mainly in language education. Vocabulary retention in one of the key issues in developing various language skills. Vocabulary instruction feedback is essential in achieving learning objectives, mainly in language education. The present study purposes to determine the role and impact of AI-driven feedback in EFL vocabulary instruction in Islamic countries educational institution. The study used systematic review method to gather data for the present study. For this, the study reviews the various AI-driven models that can be integrated with E-learning and act a source of feedback. The findings of the review assert that AI-driven mechanisms can be integrated to enhance the vocabulary learning and retention. The analysis suggest that AI-driven feedback models can useful if they are effectively incorporated in enhancing EFL vocabulary learning. By leveraging these technologies, instructors can produce more personalized feedback and operative learning experiences that help students in their vocabulary learning and retention.